Peran Perdagangan Bebas (Ekspor dan Impor) terhadap Negara Indonesia dan Negara Jepang - Nadia Ludyanti Esya Putri; Farah Nafisa Amelia; Calista Putri Fitriana; Silvi Hajar Eka; Rini Maghfiroh (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
Free trade is a central issue in global economic dynamics, particularly in the interactions between developed and developing countries. While it offers developing countries opportunities to expand exports, attract foreign investment, and stimulate economic growth, developed countries benefit through market expansion, increased competitiveness, and industrial as well as technological dominance. However, these benefits are not always evenly distributed. In the case of Indonesia, participation in free trade frameworks such as AFTA provides broader market access but also demands effective trade policies and export strategies to remain competitive. This study contributes to the discourse of Islamic law by linking global trade theories with Islamic business ethics. Accordingly, examining the role of free trade is essential to understand how both developed and developing nations can maximize its advantages while mitigating the adverse impacts of global trade liberalization.